Identifying the high potential zones for hydraulic fracture propagation / Eastern Baghdad field - Ihsan, Amani; Al- Ameri, Nagham Jasim (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
For a reservoir with high storage capacity and low ability to produce, the serious problem is the sharp reduction in the recorded well productivity within a short period. One solution to this problem is to create hydraulic fractures that increase formation permeability and keep its production at high rates for a sufficient time. The field under study is the East Baghdad oil field of three formations: Saadi, Tanuma, and Khasib. Knowing the geomechanical behavior of these reservoirs has a critical effect on the success of hydraulic fracturing operations. In this study, rock stress magnitude and direction, rock elasticity, rock strength to fracturing initiation, and all these parameters in addition to petrophysical properties will be used to identify whether the hydraulic fracturing operation could be successful or not. An integrated modeling of the studied reservoir is an essential step including 1-D geomechanical evaluation of many formations in order to choose the perfect layer to create hydraulic fracture. Then, a 3-D distribution of geomechanical properties and petrophysical properties was presented to make a perfect selection of these properties. The geomechanical evaluation of the reservoirs under study is supported by experimental evaluation of core samples including Energy Dispersive X-ray spectroscopy (EDS), Scanning Electron Microscopic (SEM) image, and thin section (TS) image. The results show that a reduction in the calculated geomechanical properties in terms of Poisson ratio young modulus and compressive strength are favorable for candidate layer selection. Among the studies of rock mechanical properties, it is also noticed that unconfined compressive strength is a crucial parameter for best layer selection. The suitable depths for fracturing jobs are given in detail in this study using brief data collected from four wells.